Significance of MRI in the diagnosis and differentiation of clear cell sarcoma of tendon and aponeurosis (CCSTA): A case report. Issue 31 (August 2018) - Sharma, Kalyan; Yadav, Sudhir Kumar; Valluru, Bimbadhar; Liu, Ling
Abstract: Rationale: Clear cell sarcoma of tendon and aponeurosis (CCSTA) or soft parts is a rare malignant melanin producing tumor entity that is derived from the neural crest cells originating from soft tissues displaying melanocytic differentiation. Diagnosis of CCSTA is difficult as it is dependent on age, size, location, necrosis, calcifications, cystic degeneration, and local to distant metastatic deposits. These tumors have very poor prognosis with a survival rate of 5–10 years because of local recurrence, early to late metastasis to lymph nodes, lungs, bones, and liver. Patient concerns: A 30-year-old Asian male has presented with a painful mass in the posterior aspect of the right ankle. He recalled of noticing an increase in the size of the lump after a traumatic insult 3 months ago. Physical examination revealed a mass of size 9x4 cm in the posterior ankle with no cutaneous ulcerative lesions. There is no history of any longstanding illness or malignancy. Diagnoses: Clear cell Sarcoma of Tendon and Aponeurosis (CCSTA) or CCS of Soft parts. Interventions: Conventional radiography demonstrated merely a soft tissue mass in the posterior compartment of the right ankle and significant calcaneal bone erosion with the sparse trabecular pattern. Plain conventional tomography showed a well-defined soft tissue heterogeneous mass with a hypoattenuating osteo-destructive focal lesion in the calcaneus. Magnetic resonance imaging (MRI) - T1 weighted imaging (T1WI) revealed an iso-intense signal relative to adjacent muscle; heterogeneous high-signal intensity on fat saturated T2 weighted imaging (T2WI). On contrast examination, lesion on T1WI, showed a heterogeneous high signal intensity, central low signal intensity with peripheral and septal enhancement. The immune-histochemistry analysis was positive for HMB-45, S-100, myoD1 and Ki67 (30%). Correlating with imaging and immune-histochemistry, a confirmatory diagnosis of CCSTA was made. Outcomes: CCSTA is typically a slowly growing painless mass in the deep soft tissues of ear, pancreas, kidney, penis, abdomen, especially in the lower extremities- Achilles tendon and aponeurosis of the ankle or in foot of young adults. As, these tumors are highly malignant, difficult to diagnose, early recognition by imaging and surgical excision are the mainstay of management. Lessons: Our case emphasizes the importance of recognizing radiological characteristics of CCSTA, and its differentiation from other soft tissue tumors, when presenting atypically. MRI plays a significant role in the diagnosis supported by histopathology and immune-histochemistry. So, radiologists should be familiar about this presentation that could guide other personnel for early detection of soft tissue tumors while including CCSTA into differential diagnosis for evaluation.